Human rights in international politics : an introduction - Wilmer, Franke (Lynne Rienner, 2015)
This comprehensive introduction to the study of human rights in international politics blends concrete developments with theoretical inquiry, illuminating both in the process. Franke Wilmer presents the nuts and bolts of human rights concepts, actors, and implementation before grappling with issues ranging from war and genocide to social and economic needs to racial and religious discrimination. Two themes the tension between values and interests, and the role of the state as both a protector of human rights and a perpetrator of human rights violations are reflected throughout the text. The result is a clear, accessible exposition of the evolution of international human rights, as well as the challenges that those rights pose, in the context of the state system.